Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The question is how to prove this equality $$\sum_{n=2}^{k} \frac{1}{n}= \sum_{n=2}^{\infty}\left(\frac{1}{n}-\frac{1}{n+k-1}\right)$$ I wasn't sure how to start proving this.

share|cite|improve this question
Start with the base case for an induction, when $k=2$. – Kevin Carlson Aug 13 '12 at 5:17
Keyword: telescoping series. – anon Aug 13 '12 at 5:18
up vote 5 down vote accepted

Write out some terms of the righthand side:

$$\begin{align*}&\left(\frac12-\frac1{k+1}\right)+\left(\frac13-\frac1{k+2}\right)+\ldots+\left(\frac1k-\frac1{2k-1}\right)\\ &+\left(\frac1{k+1}-\frac1{2k}\right)+\left(\frac1{k+2}-\frac1{2k+1}\right)+\ldots \end{align*}$$

Notice that all of the negative terms are cancelled out by positive terms later in the series: $-\frac1{k+1}$ in the first term by $\frac1{k+1}$ in the $k$-th term, $-\frac1{k+2}$ in the second term by $\frac1{k+2}$ in the $(k+1)$-st term, and so on. The only terms that are left uncancelled are the positive parts of the terms in the top line above:


This is precisely the sum on the lefthand side.

Added: The sketch above is informal and ignores the issue of convergence of the infinite series on the righthand side of the identity. For $m\ge 2$ let $$s_m=\sum_{n=2}^m\left(\frac1n-\frac1{n+k-1}\right)\;.$$ For $m\ge k$ we can carry out the cancellation above to write

$$\begin{align*}s_m&=\sum_{n=2}^k\frac1n-\sum_{n=m-k+2}^m\frac1{n+k-1}\\ &=\sum_{n=2}^k\frac1n-\sum_{n=m+1}^{m+k-1}\frac1n\;. \end{align*}$$

Now $$0\le\sum_{n=m+1}^{m+k-1}\frac1n\le\sum_{n=m+1}^{m+k-1}\frac1{m+1}=\frac{k-1}{m+1}\to 0\text{ as }m\to\infty\;,$$ so $$\lim_{m\to\infty}s_m=\sum_{n=2}^k\frac1n\;,$$ exactly as we expected from the informal argument.

share|cite|improve this answer
@BrianM.Scott: thank you so much for your details explanation! :) – DRN Aug 13 '12 at 6:06
@Norlyda: You’re welcome! – Brian M. Scott Aug 13 '12 at 6:08

We may also try this: $$\sum_{n=2}^{k} \frac{1}{n}= \sum_{n=2}^{\infty}\left(\frac{1}{n}-\frac{1}{n+k-1}\right) = \sum_{n=2}^{\infty} \frac{1}{n}-\sum_{n=2}^{\infty}\frac{1}{n+k-1}$$ $$\sum_{n=2}^{\infty}\frac{1}{n+k-1}=\sum_{n=2}^{\infty} \frac{1}{n}-\sum_{n=2}^{k} \frac{1}{n}=\sum_{n=k+1}^{\infty}\frac{1}{n}. $$


share|cite|improve this answer
Hmm, the harmonic series... one would usually be leery of subtracting two divergent series, though. – J. M. Aug 13 '12 at 11:45

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.